Power and Politics in Nigeria: An Expositions of the Hobbesian State of Nature - Kefas, Bako; Engaya, Suleiman; Anyanu, Adugba Rebecca (Kwaghe International Journal of Arts, Humanities and Religious Studies, 2024)
In the light of recent security developments in various regions of Nigeria, it is safe to assert that Nigeria is faced with a myriad of multi-dimensional security challenges, which pose threats to the country's national security. The insecurity situation in the country has led many to wonder if Nigeria has not returned to the Hobbesian state of nature where, life was solitary, nasty, brutish and short. This paper is an attempt to look critically to the insecurity problem in Northern Nigeria. This paper finds out that these security challenges are complex in nature and continually impact all the country's socio-economic development; national security, public safety and criminal justice space has also been impacted. The paper concludes that the growing rate of Nigeria’s poverty profile shows that Nigerians have been living in a state of insecurity. That a man who is not guaranteed of his welfare cannot feel secured. The study relied on secondary source of data generated from documentary sources such as journals, official publications, books chapters, newspapers and magazines as well online materials and through the lens of Thomas Hobbes Social Contract theory. This paper recommends strengthen governance and improve security measures.